Association Between Digital Health Literacy and Anemia Prevention Behavior Among Junior High School Girls in Bandung City, Indonesia - Fuadah, Fahmi (Program Studi Ilmu Kesehatan Masyarakat, Universitas Jambi, 2026)
Anemia remains a major public health problem among adolescent girls, associated with impaired physical growth, reduced cognitive performance, poor academic achievement, and long-term reproductive health risks. Although digital technology has become a primary source of health information for adolescents, evidence on the association between digital health literacy and anemia prevention behavior among Indonesian adolescent girls remains limited. This study aimed to analyze the association between digital health literacy and anemia prevention behavior among adolescent girls in Bandung City, Indonesia. A school-based cross-sectional study was conducted among 124 adolescent girls selected using simple random sampling from a junior high school in Bandung City. Data were collected using a structured questionnaire covering respondents' characteristics, the eHealth Literacy Scale (eHEALS), and an anemia prevention behavior questionnaire. Descriptive statistics, chi-square analysis, and multivariable logistic regression were performed, with significance set at p<0.05. Results showed that 67.7% of respondents had good digital health literacy and 71.8% demonstrated good anemia prevention behavior. Digital health literacy was significantly associated with anemia prevention behavior (p=0.002). After adjusting for age and grade level, girls with good digital health literacy were more likely to demonstrate good anemia prevention behavior than those with lower literacy (AOR=2.84; 95% CI=1.41–5.73; p=0.003). Digital health literacy is thus independently associated with anemia prevention behavior. Strengthening digital health literacy through school-based health education, digital health promotion, and collaboration between schools and primary healthcare centers is recommended to support anemia prevention efforts among adolescent girls.